Moskva glazami inostrantsev ("Dvuglavyi orel") . Moskva glazami inostrantsev ("Dvuglavyi orel") . Moscow Through the Eyes of Foreigners ("Double Eagle") . Москва глазами иностранцев ("Двуглавый орел") - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with an Italian diplomat and a French filmmaker living in Moscow about their impressions of Moscow and its residents. Интервью с итальянским дипломатом и французским режиссером, живущими в Москве, об их впечатлениях о Москве и москвичах.